The Accomplishment of The Rights of The Nursing Mother to Female Employees in The City of Kendari - Zuliarti, Wa Ode; Hijriani, Hijriani (International Journal of Management and Education in Human Development, 2022)
invitations and to protect nursing rights for female employees in the city of kendari. The study adopted the normative type of legal research by approach of the law. While the legal material used was the primary one covering all binding statutes based on the constitutional hierarchy, secondary legal material was obtained through interviews, and non legal material was obtained through media pranata. Research shows that companies in the city of Kendari have basically provided a lactation corner as lactation or nursing mother’s facilities. But when it comes to supporting tools and infrastructure in the corner of the felt is minimal and not in accordance with the applicable regulations of the law.